2022
DOI: 10.1096/fj.202101707r
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposome C6‐Ceramide in combination with anti‐CTLA4 antibody improves anti‐tumor immunity in hepatocellular cancer

Abstract: Combination therapy represents an effective therapeutic approach to overcome hepatocellular cancer (HCC) resistance to immune checkpoint blockade (ICB). Based upon previous work demonstrating that nanoliposome C6‐ceramide (LipC6) not only induces HCC apoptosis but also prevents HCC‐induced immune tolerance, we now investigate the potential of LipC6 in combination with ICB in HCC treatment. We generated orthotopic HCC‐bearing mice, which have typical features in common with human patients, and then treated them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…There is a subject of controversy regarding the growth inhibition of C6 ceramide in cancer cells through the apoptotic pathway. Several studies have discovered C6 ceramide-induced apoptosis by evaluating cleaved caspase 3 and/or PARP, such as those on hepatocellular cancer [21], cutaneous T cell lymphoma [22], and pancreatic cancer [23]. On the contrary, studies on head and neck squamous cell carcinoma, melanoma, and breast cancer have revealed that the proliferative inhibitory effect of C6 ceramide is not associated with apoptosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…There is a subject of controversy regarding the growth inhibition of C6 ceramide in cancer cells through the apoptotic pathway. Several studies have discovered C6 ceramide-induced apoptosis by evaluating cleaved caspase 3 and/or PARP, such as those on hepatocellular cancer [21], cutaneous T cell lymphoma [22], and pancreatic cancer [23]. On the contrary, studies on head and neck squamous cell carcinoma, melanoma, and breast cancer have revealed that the proliferative inhibitory effect of C6 ceramide is not associated with apoptosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pegylated poly (lactic-co-glycolic acid) (PLGA) NPs encapsulating a combined heparanase T cell epitope alone or in combination with TLR3 and TLR7 ligands can be combined with an anti-DEC-205 (CD205) antibody to target DCs [194]. A study in our lab also showed that LipC6, in combination with an anti-CTLA4 antibody, significantly inhibited HCC growth by increasing the infiltration of CD8 T cells [195].…”
Section: Frontiers and Prospectsmentioning
confidence: 96%
“…The dysregulation of sphingolipid metabolism is also frequently associated with cancer stem cells ( 103 , 104 ) and consequently generates a series of tumor immune-related effects; this situation suggests that ceramide is a key player in cancer immunotherapy ( 104 ). Elevated levels of ceramides induce cancer cell death ( 105 ), enhance the host protective immune response, and induce cancer regression ( 101 , 106 ). Elevated levels of S1P induce an increase in the antiapoptotic proteins Bcl-2 and Bcl-XL in macrophages and the M2-type polarization of macrophages, which can also recruit immune cells to immune tissues for immune action ( 107 , 108 ).…”
Section: The Relationship Between Sphingolipid Metabolism and Tumor I...mentioning
confidence: 99%